Optimal azimuth positioning algorithm for base station antenna based on Gaussian distribution - Songbai LIANG; Feng CHEN; Haiping SONG; Wensheng LI (Dianxin kexue)
In order to improve the accuracy and efficiency of the discovery of the antenna-feeder problem,an optimal direction angle solution based on Gaussian distribution was proposed to diagnose the antenna-feeder coverage problems of operators.First of all,the location direction information between each MR sampling point reported by the UE and the base station was calculated,and then the proportion of MR sampling points in each interval was calculated,Based on the Gaussian distribution feature,the angle range with the largest proportion of MR sampling points was the appropriate azimuth,which was based on the user hotspot distribution of the sector.Finally,the date of optimal azimuth was compared with the base station azimuth in the background antenna database to detect antenna feeder problems,such as cross feeder,improper antenna coverage direction and incorrect background antenna database,and so on.The field verification shows that,the cost,accuracy and efficiency of the antenna-feeder problems are obviously improved compared with the existing methods.